Penentuan Prioritas Strategi untuk Meningkatkan Kinerja Layanan Bank Sampah X Menggunakan Metode Analytical Hierarchy Process (AHP) - Fely Eka Sonia; Rizki Andre Handika; Winny Laura Christina Hutagalung (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The waste management problem in Indonesia, especially in Sungai Penuh City remains a complex and ongoing challenge. The increasing population causes a continuous rise in waste volume, negatively impacting environmental quality and community activities. The x waste bank was established as an initiative to enhance education and community involvement in waste management and recycling with the goal of creating a clean, healthy and comfortable environment in Sungai Penuh City. This study shows that the composition of inorganic waste bank at X waste bank varies, including plastic, paper, metal and other types of waste. Each type of waste exhibits different generation patterns each month. Paper waste is the largest contributor, accounting for 69% of the total waste collected from January to June. Next is plastic waste, the second largest contributor at 15%. The remaining two types, metal waste and other waste, have relatively smaller proportions amounting to 8% of the total. Additionally, one point to emphasize is the need to increase the service performance at X waste bank and new facilities that are currently unavailable, to encourage more residents of Sungai Penuh City. Based on the ranking results calculated using the Analytical Hierarchy Process (AHP) methode, there is one point that needs to be emphasized in order to improve service performance at Waste Bank X, namely by adding new facilities that are not yet available.